The Future of Antarctica: Sam Bateman's Contribution to Antarctic Geopolitics - Marcus Haward; Jeffrey McGee; Anthony Press (2023)
Sam Bateman’s deep interest in security and the law of the sea inevitably led him to consider the geopolitical context of the vast region to Australia’s south, Antarctica and the Southern Ocean. After all, the Antarctic Treaty System (ATS) provides a security and governance framework to Australia’s south that has directly impacted Australia’s defence posture, resource security, and its status as an Antarctic claimant state. Born from the tensions of the Cold War, the 1959 Antarctic Treaty,1 sets aside international argument over Antarctic sovereignty claims through the provisions of Article iv, that both protects the status of the seven sovereignty claims and provides accommodation for those states not recognising them. For Australia, this was a key feature of the treaty.2 The non-militarisation provisions of the treaty are also integral to Australia’s national security (see below), allowing Australia to focus its defence assets on northern regions of greater security threat. With close colleague Anthony Bergin, Sam was one of the Australian few academic commentators on the Antarctic and the Southern Ocean who approached the issue through the lens of strategic studies. Recognising the rise in the capabilities of remote satellite and ocean technologies, as well as global drivers such as resource and food security, Sam began to look at implications of changing security environment for the Antarctic.